Malta : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2019)
This Financial System Stability Assessment of Malta shows that while Malta has benefited from considerable financial inflows, the associated risks, especially related to money laundering and terrorism financing, need to be closely monitored and addressed. Key metrics suggest that the banking system is in good health, but challenges exist. The banking system remains resilient under a severe scenario, with weaknesses limited to a few small banks. The system is sufficiently capitalized to absorb losses in the event of a severe macroeconomic shock, but risky exposures would lead to potential losses at a few small banks. The analysis suggests that ensuring adequate resources is critical to preserve the effectiveness and operational independence of the Malta Financial Services Authority (MFSA). In order to strengthen bank supervision, the MFSA should take timelier supervisory actions, increase the frequency of onsite inspections, make more use of monetary fines as part of the sanctioning regime, and ensure supervisory action is not delayed through judicial appeal.